EEG Patterns in Patients With Calcified Neurocysticercosis With or Without Hippocampal Atrophy. Issue 4 (July 2018) - Issa, Naoum P.; Sedler, Mark J.; Del Brutto, Victor J.; Darsan, Elizabeth; Milla, Lucía; Montes, Jessica; Zambrano, Mauricio; Del Brutto, Oscar H.
Abstract : Purpose: To assess whether hippocampal atrophy develops in conjunction with clinical or subclinical epileptiform or encephalopathic activity in subjects with neurocysticercosis (NCC). Methods: Using a population-based and nested case–control study design, scalp EEGs and brain MRIs were performed in Atahualpa residents aged ≥40 years, who have imaging-confirmed NCC (case patients), as well as in age- and sex-matched NCC-free control subjects. Results: Sixty-two case patients and 62 control subjects were included. Encephalopathic EEG patterns were more common in five NCC subjects with epilepsy than in those without a history of seizures. Epileptiform EEG activity was noted in one patient with NCC but in none of the control subjects. This subject's focal epileptiform discharges correlated with the location of calcified cysticerci in the brain parenchyma, and the hippocampus ipsilateral to the epileptiform discharges was more atrophic than the contralateral hippocampus. The degree of hippocampal atrophy in patients with NCC without a history of seizures was significantly greater than in control subjects ( P < 0.01) and tended to be even greater in patients with NCC with a history of seizures. Conclusions: Hippocampal atrophy may not be exclusively related to seizure activity in patients with NCC. Other mechanisms, such as recurrent bouts of inflammation around calcified cysticerci, might explain the association between NCC and hippocampal atrophy.